Autism Spectrum Disorder in Infancy and Early Childhood: The Model of the Centro de Estudos do Bebé e da Criança for Diagnosis and Therapeutic Intervention - Martins Halpern, Cristina (2021)
Introduction: The Centro de Estudos do Bebé e da Criança in Hospital Dona Estefânia has organized a multidisciplinary model for children under three with suspected autism spectrum disorder, thus implementing the recent guidelines established by the Directorate General for Health. The aim of this study is to describe this model and case series.Material and Methods: A retrospective descriptive study of observed children with suspected ASD. They were observed according to the model of the Centro de Estudos do Bebé e da Criança and DC:0-5TM classification, between January 2018 and September 2019.Results: The study included 178 children. The average age at the initial assessment was 27 months. From the total sample, 116 children concluded the diagnostic sessions (axis I): Autism Spectrum Disorder/Early Atypical (36%), Developmental Language Disorder (18%), Other (19%). Factors of axes II, III, IV and V of DC:0-5TM were determinant for clinical diagnosis in 26%.Discussion: Of 116 children, 36% were diagnosed with Autism Spectrum Disorder. This highlights the diagnostic challenge posed by neurodevelopmental disorders in early infancy. The sample shows that the characteristics of the relationship with the caregiver (axis II), presence of physical conditions (axis III), psycho-social stressors (axis IV) and developmental trajectory (axis V) have a significant clinical impact. In the future, the initial assessment should take place well before the age of 27 months because of the impact on prognosis.Conclusion: This model is a pioneering approach in Portugal. It promotes a common approach of Child and Adolescent Psychiatry and Neuropediatrics/Developmental Pediatrics in early infancy. Moreover, it increases the diagnostic acuity of Autism Spectrum Disorders and early therapeutic intervention.